2018
DOI: 10.1038/s41591-018-0161-0
|View full text |Cite
|
Sign up to set email alerts
|

Route of immunization defines multiple mechanisms of vaccine-mediated protection against SIV

Abstract: Antibodies are the primary correlate of protection for most licensed vaccines; however, their mechanisms of protection may vary, ranging from physical blockade to clearance via the recruitment of innate immunity. Here, we uncover striking functional diversity in vaccine-induced antibodies that is driven by immunization site and is associated with reduced risk of SIV infection in nonhuman primates. While equivalent levels of protection were observed following intramuscular (IM) and aerosol (AE) immunization wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
168
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 66 publications
(86 reference statements)
8
168
2
Order By: Relevance
“…We next sought to evaluate the generality of the observation that humoral response quality, beyond magnitude alone, is important in analyzing protection. Recently, Fc Array and functional measurements were collected for animals in a distinct SIV vaccine study (employing a DNA prime‐Ad5 boost vaccine regimen), and the analysis pointed to strikingly different antibody properties and correlates of protection associated with different routes of vaccination (Ackerman et al , ). In that study, animals vaccinated with a SIVmac239 Env immunogen (administered either intramuscularly or mucosally) exhibited significantly better protection against infection compared to those vaccinated with a mosaic Env immunogen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We next sought to evaluate the generality of the observation that humoral response quality, beyond magnitude alone, is important in analyzing protection. Recently, Fc Array and functional measurements were collected for animals in a distinct SIV vaccine study (employing a DNA prime‐Ad5 boost vaccine regimen), and the analysis pointed to strikingly different antibody properties and correlates of protection associated with different routes of vaccination (Ackerman et al , ). In that study, animals vaccinated with a SIVmac239 Env immunogen (administered either intramuscularly or mucosally) exhibited significantly better protection against infection compared to those vaccinated with a mosaic Env immunogen.…”
Section: Resultsmentioning
confidence: 99%
“…Here, protection was modeled with a multi‐dimensional, multi‐group CoxPH survival model, combining animals from all adjuvant groups and employing aggressive feature filtering, to incorporate only a small number of features. The use of a Cox modeling approach follows that used in recent studies (Bradley et al , ; Ackerman et al , ), so as to avoid having to discretize protection levels (Chung et al , ; Vaccari et al , ). We found that to avoid overfitting, it was necessary to perform feature pre‐filtering and employ greedy feature elimination methods to narrow down the number of features used by the Cox model (Frejno et al , ); regularization techniques (Simon et al , ) displayed substantially poorer performance, resulting in empty models (i.e., with no features selected), likely due to the semi‐parametric formulation of the Cox PH model and the small sample size of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, passive transfer of the combination of a systemically administered anti-HIV IgG1 and a mucosally administered anti-HIV dimeric IgA2 provided complete protection against a high-dose rectal SHIV challenge while transfer of the anti-HIV IgG1 alone was not protective (5), suggesting that the combination of systemic and mucosal anti-HIV IgG and IgA, respectively, may be required for maximum protection. Another recent study demonstrated that systemic (intramuscular) and mucosal (aerosol) immunization with the same vaccine induced equivalent levels of protection against SIV challenge(6). However, evaluation of vaccine-induced immune responses determined that protection induced by intramuscular immunization was associated with serum IgG-mediated immune responses while protection induced by aerosol immunization was associated with serum IgA-mediated immune responses(6) Therefore, optimizing both systemic and mucosal immunization regimens may be required to provide consistent protection against mucosal HIV transmission(7).…”
Section: Introductionmentioning
confidence: 99%